H1N1 influenza vaccination during pregnancy and fetal and neonatal outcomes - Fell, Deshayne B; Sprague, Ann E; Liu, Ning; Yasseen, Abdool S; Wen, Shi-Wu; Smith, Graeme; Walker, Mark C (Université d'Ottawa | University of Ottawa, 2012)
We evaluated the relationship between maternal H1N1 vaccination and fetal and neonatal outcomes among singleton births during the 2009-2010 H1N1 pandemic. Methods. We used a population-based perinatal database in Ontario, Canada, to examine preterm birth (PTB), small-for-gestational-age (SGA) births, 5-minute Apgar score below 7, and fetal death via multivariable regression. We compared outcomes between women who did and did not receive an H1N1 vaccination during pregnancy. Results. Of the 55 570 mothers with a singleton birth, 23 340 (42.0%) received an H1N1 vaccination during pregnancy. Vaccinated mothers were less likely to have an SGA infant based on the 10th (adjusted risk ratio [RR] = 0.90; 95% confidence interval [CI] = 0.85, 0.96) and 3rd (adjusted RR = 0.81; 95% CI = 0.72, 0.92) growth percentiles; PTB at less than 32 weeks’ gestation (adjusted RR = 0.73; 95% CI = 0.58, 0.91) and fetal death (adjusted RR = 0.66; 95% CI = 0.47, 0.91) were also less likely among these women. Conclusions. Our results suggest that second- or third-trimester H1N1 vaccination was associated with improved fetal and neonatal outcomes during the recent pandemic. Our findings need to be confirmed in future studies with designs that can better overcome concerns regarding biased estimates of vaccine efficacy.